2018
DOI: 10.1002/cmdc.201800031
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin Mimetics as Anti‐β‐Amyloid Agents: A Comparison of Peptide and Protein Approaches

Abstract: β-Amyloid (Aβ) aggregation is causally linked to neuronal pathology in Alzheimer’s disease; therefore, several small molecules, antibodies, and peptides have been tested as anti-Aβ agents. We developed two compounds based on the Aβ-binding domain of transthyretin (TTR): a cyclic peptide cG8 and an engineered protein mTTR, and compared them for therapeutically relevant properties. Both mTTR and cG8 inhibit fibrillogenesis of Aβ, with mTTR inhibiting at a lower concentration than cG8. Both inhibit aggregation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…[1b, 24b] Our findings provide am olecular basis for understanding their function and should thus assist in the design of novel potent anti-amyloid drugs.I na ddition, they may contribute to elucidating the mechanism of previously reported self-assembling peptide inhibitors designed to mimic surfaces involved in self-or cross-amyloid interactions,f or which the mode of action is thus far not understood. [29]…”
Section: Resultsmentioning
confidence: 99%
“…[1b, 24b] Our findings provide am olecular basis for understanding their function and should thus assist in the design of novel potent anti-amyloid drugs.I na ddition, they may contribute to elucidating the mechanism of previously reported self-assembling peptide inhibitors designed to mimic surfaces involved in self-or cross-amyloid interactions,f or which the mode of action is thus far not understood. [29]…”
Section: Resultsmentioning
confidence: 99%
“…This approach allowed to identify cG8 (Figure 4), a cyclic peptide which demonstrated in multiple complementary techniques to cluster Aβ into large weakly associated aggregates, thus blocking Aβ in a non-fibrillar aggregation stage and accelerating the Aβ clearance by natural mechanisms [154]. In a study comparing protein versus peptide [155], each designed as a mimic of the Aβ-binding domain on wild-type TTR, both mTTR (engineered protein) and cG8 (cyclic peptide) resulted effective at inhibiting amyloid formation by either Aβ isoform, Aβ 1-40 and Aβ 1-42. The results obtained by ThT fluorescence spectroscopy showed that mTTR and cG8 are not broad-spectrum antiamyloid agents, because they recognize similar epitopes that Aβ and amylin share but that αsynuclein does not possess.…”
Section: Ttr-aβ Interaction-based Strategies To Design Anti-aβ Agentsmentioning
confidence: 99%
“…Nevertheless, mTTR has the advantage to be more effective to lower concentration, having a strong impact on both the morphology and the quantity of Aβ deposits on cell, while cG8, thanks to its smaller size, results in better stability against proteolysis and less interferences from nonspecific biological materials. It is hypothesized that the greater efficacy of mTTR is attributable to a relative stable anti-parallel two β-strand conformation that fully mimics TTR's Aβ binding site, while cG8 shows a conformational heterogeneity [155]. These findings In a study comparing protein versus peptide [155], each designed as a mimic of the Aβ-binding domain on wild-type TTR, both mTTR (engineered protein) and cG8 (cyclic peptide) resulted effective at inhibiting amyloid formation by either Aβ isoform, Aβ 1-40 and Aβ 1-42.…”
Section: Ttr-aβ Interaction-based Strategies To Design Anti-aβ Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition occurs at substoichiometric quantities of mTTR, via selective binding to oligomeric Aβ (Yang et al, 2013), indicating promise as a possible therapeutic compound. mTTR significantly reduces adherence of oligomeric Aβ to human iPSC-derived neurons (Pate et al, 2018), likely explaining its mechanism of protection against Aβ toxicity.…”
Section: Introductionmentioning
confidence: 98%